Chemistry Design Towards a Stable Sulfide‐Based Superionic Conductor Li4Cu8Ge3S12. Issue 23 (29th April 2019) - Wang, Yingqi; Lü, Xujie; Zheng, Chong; Liu, Xiang; Chen, Zonghai; Yang, Wenge; Lin, Jianhua; Huang, Fuqiang
Abstract: Sulfide‐based superionic conductors with high ionic conductivity have been explored as candidates for solid‐state Li batteries. However, moisture hypersensitivity has made their manufacture complicated and costly and also impeded applications in batteries. Now, a sulfide‐based superionic conductor Li4 Cu8 Ge3 S12 with superior stability was developed based on the hard/soft acid–base theory. The compound is stable in both moist air and aqueous LiOH aqueous solution. The electrochemical stability window was up to 1.5 V. An ionic conductivity of 0.9×10 −4 S cm with low activation energy of 0.33 eV was achieved without any optimization. The material features a rigid Cu‐Ge‐S open framework that increases its stability. Meanwhile, the weak bonding between Li + and the framework promotes ionic conductivity. This work provides a structural configuration in which weak Li bonding in the rigid framework promotes an environment for highly conductive and stable solid‐state electrolytes. Abstract : Chemical design of an ionic conductor : A type of sulfide‐based superionic conductor has been developed based on the hard/soft acid–base theory. The as‐prepared Li4 Cu8 Ge3 S12 compound possesses a unique structural configuration where the weakly‐bonded Li in a rigid framework endues both high conductivity and outstanding stability.